The Transformation of the Aceh Community's Response to Rohingya Refugees and Its Relevance to Aceh Qanun Number 6 of 2008 in Population Administration - Dessy Asnita; Faisal Faisal; Anizar Anizar (Tunas Institute, 2025)
This study discusses the changing attitudes of the Acehnese community towards Rohingya refugees and its implications for the legal protection of refugee families in the context of Islamic family law. The shift in community responses from positive to negative attitudes, manifested through demonstrations, expulsions, and verbal and physical violence, has led to the marginalization of refugees, including their families. This article connects this situation to the implementation of Aceh Qanun Number 6 of 2008, Article 27, which governs the role of the Population and Civil Registration Office to coordinate with the Religious Affairs Office (KUA) and the Religious Court in registering marriages. The absence of official documentation for refugees becomes a major obstacle, impacting the registration of marriages and legal protection of their families. This situation worsens the family’s rights in Islam, particularly their legitimate marital status. This research uses a qualitative method with a mixed approach, involving interviews, social media analysis, and legal reviews. The results reveal that factors such as past trauma, difficulties in integration, hoaxes, and the role of social media in spreading hate speech have contributed to the change in attitudes. The significant impact of this change is seen in the family law context, where refugee families face legal uncertainty regarding marriage matters. This study focuses on the role of the values of ukhuwah Islamiyah and sharia principles, which should serve as the foundation in protecting the rights of refugee families. The government is expected to take decisive steps in providing legal certainty and protection for refugees wishing to marry, whether between refugees or between refugees and local citizens, and to encourage the community to treat them with humanity in accordance with Islamic teachings.